2015
DOI: 10.1016/j.molp.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Ovary-to-Fruit Transition is Characterized by a Spatial Shift of mRNAs for Cell Wall Invertase and its Inhibitor with the Encoded Proteins Localized to Sieve Elements

Abstract: Central to understanding fruit development is to elucidate the processes mediating a successful transition from pre-pollination ovaries to newly set fruit, a key step in establishing fruit yield potential. In tomato, cell wall invertase (CWIN) LIN5 and its inhibitor INH1 are essential for fruit growth. However, the molecular and cellular basis by which they exert their roles in ovary-to-fruit transition remains unknown. To address this issue, we conducted a study focusing on ovaries and fruitlets at 2 days bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 47 publications
3
64
0
Order By: Relevance
“…Measurement of enzyme activities in ovaries at 2 d before pollination (dbp) and fruits at 2 dap, the key stages determining fruit set and yield potential (Palmer et al, 2015), revealed there was a 35% to 41% increase of CWIN activity in the transgenic 2-dbp ovaries and 2-dap fruits under both control and LMHS conditions compared with that from wild-type plants (Fig. 3A).…”
Section: Cwin-elevated Transgenic Tomato Was Characterized By Sustainmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of enzyme activities in ovaries at 2 d before pollination (dbp) and fruits at 2 dap, the key stages determining fruit set and yield potential (Palmer et al, 2015), revealed there was a 35% to 41% increase of CWIN activity in the transgenic 2-dbp ovaries and 2-dap fruits under both control and LMHS conditions compared with that from wild-type plants (Fig. 3A).…”
Section: Cwin-elevated Transgenic Tomato Was Characterized By Sustainmentioning
confidence: 99%
“…In tomato, for example, cultivars with higher CWIN activity in anther and fruit had a lower fruit abortion rate under heat stress compared to cultivars with lower CWIN activity Li et al, 2012), and an increase in CWIN activity was observed during ovaryto-fruit transition (Palmer et al, 2015). However, it remains to be seen whether genetically increasing CWIN activity can indeed improve fruit and seed set under heat stress and, if so, what is the underlying physiological and molecular basis.…”
mentioning
confidence: 99%
“…9). Pertinently, VIN is the major enzyme hydrolyzing Suc in tomato pericarp at the cell division stage (Beauvoit et al, 2014), when unloading occurs symplasmically (Palmer et al, 2015).…”
Section: Vin Contributes To Male Fertility Probably By Impacting Starmentioning
confidence: 99%
“…Cell wall invertase does not show localization in tomato ovaries before flowering, but interestingly does localize in the fruit vascular tissues at fruit set to transduce the glucose signal by supporting sugar unloading to the fruit, promoting cell division and the resultant fruit set (Palmer et al, 2015). Therefore, the vascular tissue-specific expression of the V-PPase gene may be related to this mechanism involving cell wall invertase because V-PPase may play a role in sugar accumulation, as described above.…”
Section: Roles Of Proton Pumps Sugars and Auxin In Fruit Set And Eamentioning
confidence: 99%